Analysis of Factors Affecting Rice Farmers' Decisions in Choosing Pesticides (Case Study in Bantimurung Subdistrict, Maros Regency) - Nurul Nisa’a Amin (Publikasi Indonesia, 2026)
Pesticides are essential agricultural inputs used to control pests and diseases in rice cultivation. However, improper selection and use of pesticides can lead to pest resistance, environmental pollution, and adverse effects on human health. Therefore, understanding the factors influencing farmers’ decisions in choosing pesticides is crucial to promoting effective usage and sustainable agricultural practices. This study aims to identify and analyze the factors that influence rice farmers’ decisions in selecting pesticides in Bantimurung District, Maros Regency. The research employed a quantitative survey method by distributing questionnaires to 50 rice farmers who actively use pesticides. The independent variables examined were age, education level, farming experience, income, and land area. Data were analyzed using multiple linear regression to determine the influence of these variables on farmers’ pesticide selection decisions. The findings indicate that education, farming experience, income, and land area significantly influence rice farmers’ decisions in purchasing pesticides, while age does not have a significant effect on the decision-making process. Farmers’ socio-economic and farming-related characteristics play an important role in pesticide selection decisions. Strengthening farmers’ education and improving economic capacity may contribute to more rational and sustainable pesticide use in rice farming.